Perception of users with physical deficiency assisted by NASF-AB about your health conditions (Research, Society and Development, 2020)
The Expanded Family Health Center (NASF-AB) was created to support the insertion of the Family Health Strategy (ESF) into the service network and expand Primary Health Care (APS) actions in Brazil. The study aimed to investigate the health conditions of users with physical disabilities, who are assisted by NASF-AB in the municipality of the coast of Paraíba. It is a field research of the exploratory and descriptive type, with a qualitative approach. We interviewed 21 users who had some kind of physical disability, where the size of the sample followed the saturation of responses criteria. There was difficulty in access and the need for monitoring (social, health and family) of the users in the APS units, becoming a challenge for a good assistance. Potentialities were observed regarding the positive perception of the users regarding home care and visits made by health professionals, constituting them as facilitators for access to family health. Therefore, there is a need to improve the access of physically disabled users to APS, by the possibility of increasing knowledge about the proposal and organization of NASF-AB and, consequently, optimizing care with health conditions.